2003
DOI: 10.1038/sj.leu.2402892
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HOX11 in childhood T-lineage acute lymphoblastic leukaemia can occur in the absence of cytogenetic aberration at 10q24: a study from the Children's Cancer Group (CCG)

Abstract: Clonal genetic aberrations in tumour cells provide critical information for the development of new diagnostic and therapeutic strategies for patients. In paediatric T-cell acute lymphoblastic leukaemia (T-ALL) chromosomal translocations are present in 30-35% of cases. HOX11 and the closely related HOX11L2 genes play a key role in T-ALL. HOX11 is aberrantly activated by either of the two chromosomal translocations, t(7;10) and t(10;14). In this study, HOX11 expression levels were measured by real-time quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 35 publications
(38 reference statements)
1
61
0
Order By: Relevance
“…In a large pediatric study a positive prognostic impact has been shown for t (10;14). 23 Two other studies have indicated a trend toward a better outcome in children with high HOX11 expression. 8,24 Ferrando et al 17 found an improved OS in 16 HOX11-positive of 52 adult patients and suggested that they might be at greater risk from treatment related mortality of allografting.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 99%
“…In a large pediatric study a positive prognostic impact has been shown for t (10;14). 23 Two other studies have indicated a trend toward a better outcome in children with high HOX11 expression. 8,24 Ferrando et al 17 found an improved OS in 16 HOX11-positive of 52 adult patients and suggested that they might be at greater risk from treatment related mortality of allografting.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 99%
“…Aberrant activation of HOX11 can be achieved by a t(10;14)(q24;q11) chromosome rearrangement, juxtaposing the HOX11 gene downstream of the T-cell receptor (TCR) a/d regulatory elements (Dube´et al, 1986(Dube´et al, , 1991. While the t(10;14) translocation is seen in only 4-7% of reported T-ALL cases, a recent study revealed elevated HOX11 expression levels in leukemic blasts in B50% (37/76) of pediatric T-ALL cases (Kees et al, 2003). Moreover, an additional 30% of pediatric T-ALLs exhibited inappropriate activation of the related HOX11 gene, HOX11L2 (Mauvieux et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…HOX11 was originally isolated from the site of the recurrent t(10;14)(q24;q11) translocation in T-ALL (Dube et al, 1991;Hatano et al, 1991;Kennedy et al, 1991;Lu et al, 1991;Dear et al, 1993) and is aberrantly expressed in 3-5% of pediatric and up to 30% of adult T-ALL cases (Berger et al, 2003;Ferrando and Look, 2003;Kees et al, 2003). Similar to other HOX genes, HOX11 plays an important role in embryonic development, and functions as a master transcriptional regulator necessary for the genesis of the spleen (Roberts et al, 1994;Dear et al, 1995).…”
Section: Aberrant Protein Expression In T-cell Acute Lymphoblastic Lementioning
confidence: 99%